Participatory Research to Address Societal Challenges and Radicalisation: an introduction - Daher, Liana; Gianni, Robert; Antonelli, Francesco (Italian Sociological Review, 2025)
This special issue aims to explore and understand the role of participatory practices to address great societal challenges. The focus of this special issue will revolve around the methodology of social labs as real-world practices aimed at promoting social inclusion, countering radicalisation, and bolstering local resilience. The radicality of the asymmetries present in society tends to generate phenomena of social marginalization and exclusion that generate resentment amongst the affected individuals. Such anger can severely affect the processes of interaction between individuals and their integration in the social fabric. Dynamics of violent extremism and polarisation are just two examples of the most impelling challenges threatening social cohesion that must be countered. Because of their persistence and increased intensity, societal challenges like the ones of violent radicalization and polarisation have increasingly gained the attention of national, supranational, and transnational institutions. However, the inherent complexity of issues related to radicalization and polarization, their pervasive presence in various social spheres, and the influence of new digital technologies, one-size-fits-all policies may prove insufficient in the overarching effort to counteract these phenomena. Consequently, existing policies could greatly benefit from innovative approaches that integrate contemporary scientific and political expertise with the knowledge, experiences, and needs of individuals involved or affected by dynamics of social exclusion. The Special Issue encompasses four interconnected tasks, one methodological and three empirical, offering a unique perspective on fostering inclusivity and understanding local responses to violent radicalisation and polarisation. The contributions will shed a light on the method and implementation of Social Labs, highlighting the opportunities and the challenges related to such methodology. Empirical contributions will operate such analysis on the basis of a comparative reconstruction of their successes and failures, and insights on embedding social inclusion into policies addressing great societal challenges like violent radicalization and polarisation.